2015
DOI: 10.1103/physrevb.91.184206
|View full text |Cite
|
Sign up to set email alerts
|

Finite-size scaling and multifractality at the Anderson transition for the three Wigner-Dyson symmetry classes in three dimensions

Abstract: The disorder induced metal-insulator transition is investigated in a three-dimensional simple cubic lattice and compared for the presence and absence of time-reversal and spin-rotational symmetry, i.e. in the three conventional symmetry classes. Large scale numerical simulations have been performed on systems with linear sizes up to L = 100 in order to obtain eigenstates at the band center, E = 0. The multifractal dimensions, exponents Dq and αq, have been determined in the range of −1 ≤ q ≤ 2. The finite-size… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 29 publications
(54 reference statements)
19
56
0
Order By: Relevance
“…Here "unitary" refers to the symmetry class of the model in the Random Matrix Theory (RMT) classification of random matrix ensembles [42], which is shared by the staggered Dirac operator [35]. A study of the multifractal properties of the eigenmodes at criticality [43] confirmed the result for the critical exponent, and also showed that the multifractal exponents of the critical eigenmodes in QCD are compatible with those of the 3D unitary Anderson model [44]. This provided further evidence that the delocalisation transitions in the two models belong to the same universality class.…”
Section: Jhep02(2017)055supporting
confidence: 56%
“…Here "unitary" refers to the symmetry class of the model in the Random Matrix Theory (RMT) classification of random matrix ensembles [42], which is shared by the staggered Dirac operator [35]. A study of the multifractal properties of the eigenmodes at criticality [43] confirmed the result for the critical exponent, and also showed that the multifractal exponents of the critical eigenmodes in QCD are compatible with those of the 3D unitary Anderson model [44]. This provided further evidence that the delocalisation transitions in the two models belong to the same universality class.…”
Section: Jhep02(2017)055supporting
confidence: 56%
“…Our methods and notations are essentially the same as in Ref. 23, to which we refer the reader for a more detailed discussion. There is however one important difference, concerning the way in which the transition is approached.…”
Section: Finite-size Scaling Laws For Generalized Multifractal Exmentioning
confidence: 99%
“…In recent high-precision calculations [22][23][24] , MFSS has been successfully employed to determine the MFEs of critical eigenfunctions, as well as to obtain a more precise estimate of the critical disorder and of the critical exponents, for Anderson models in different symmetry classes. In this work we want to perform a similar MFSS analysis to study the Anderson localizationdelocalization transition in the spectrum of the Dirac operator in QCD.…”
Section: Finite-size Scaling Laws For Generalized Multifractal Exmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a generalised multifractal analysis has been used to perform high-precision studies of the critical properties of the transition in the non-interacting case [17][18][19][20][21][22]. This formalism is also potentially applicable in the presence of interactions, and work along this line is currently being pursued [23,24].…”
Section: Multifractal Formalismmentioning
confidence: 99%